Optimization Analysis of The Strength Capacity and The Economic Value Comparison of Castellated Steel Beam and Its Equivalent IWF Beam - Budi, Listiyono; Widodo, Aris; Haryadi, Bambang; Endroyo, Bambang; Wicaksono, Dimas; Subagio, Triono (Universitas Negeri Semarang, 2021)
The research is aimed to figure out the comparison of the strength capacity and economic value comparison of castellated steel beam to its equivalent IWF beam. The profile of the castellated steel beam in this study included all profiles of castellated steel beam on the market based on the products catalog of the castellated steel beam from PT. Gunung Garuda. The finite element method was used in this study with the aid from Abaqus program to get a comparison of the strength capacity of castellated steel beam to its equivalent IWF beam. The next stage next involved the calculation of a comparison of the economic value of the castellated steel beam with hexagonal holes with to its equivalent IWF beam. The results of the study showed that the castellated steel beam experienced an increase in the strength capacity of 1,189 up to 2,330 times compared to its equivalent IWF beam. The comparison of the strength capacity between the castellated steel beam and its equivalent IWF beam is at 1,010 up to 1,539. Based on the combination between the comparison of strength capacity and the economic value, there are 14 (58.33%) profiles of the castellated steel beam which is categorized as efficient in terms of the design of the structure and cost, there are four (16.67%) profiles of the castellated steel beam which is categorized as efficient in terms of the design of the structure but not efficient in terms of cost, and there are 6 (25.00%) profiles of the castellated steel beam which is categorized as inefficient in terms of the design of the structure and cost. The results of this study indicate that the castellated steel beam can replace its equivalent IWF beam. Selection of profile of the castellated steel beam is appropriate to provide efficiency in terms of weight of the structure between 58.5% to 15.1% and can provide efficiency in terms of cost of between 48.4% to 0.9%.